Management of Cerebral Concussion in Sports: The Athletic Trainer's Perspective - Oliaro, Scott (National Athletic Trainers' Association, Inc., 2001)
OBJECTIVE: To present a new approach in the evaluation and management of concussion from the athletic trainer's perspective. BACKGROUND: The evaluation and management of concussion continues to be a controversial topic among sports medicine professionals. Inconsistent management, lack of objective data, and confusion concerning assessment techniques may lead to inappropriate decisions regarding when to return an athlete to competition after concussion. In this article, we provide recommendations and considerations for the certified athletic trainer in the management of concussion. We also present a quantifiable assessment technique that provides more information on which return-to-play decisions can be made; this technique can be used during the initial sideline examination as well as during subsequent follow-up examinations. RECOMMENDATIONS: Certified athletic trainers and team physicians should consistently use appropriate grading scales. Assessment of concussion should include a symptom checklist, the Balance Error Scoring System, and the Standardized Assessment of Concussion, and the results should be compared with the athlete's normal baseline scores. Follow-up neuropsychological and postural stability testing is recommended. Return-to-play decisions should be based on the grade of concussion, scores on objective tests, and presence of concussive symptoms during exertional activities.